![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Theo đề bài ta có:
\(\frac{a+28}{b}=\frac{a}{b}+\frac{28}{b}=\frac{24}{23}\)
Mà \(\frac{a}{b}=\frac{4}{5}\)
\(\frac{28}{b}=\frac{24}{23}-\frac{4}{5}=\frac{28}{115}\)
\(\Rightarrow b=115\)
\(\Rightarrow\frac{a}{115}=\frac{4}{5}=\frac{92}{115}\)
Vậy \(\frac{a}{b}=\frac{92}{115}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\frac{70}{24}+x-\frac{53}{24}\right):\frac{4}{3}=1\)
\(\left(\frac{70}{24}+x-\frac{53}{24}\right)=\frac{4}{3}\)
\(\frac{70}{24}+x=\frac{4}{3}+\frac{53}{24}\)
\(\frac{70}{24}+x=\frac{32}{24}+\frac{53}{24}\)
\(\frac{70}{24}+x=\frac{88}{24}\)
\(x=\frac{88}{24}-\frac{70}{24}\)
\(x=\frac{18}{24}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1}{4}\)+ x : 4 =\(\frac{3}{4}\)
\(\frac{1}{4}\)+ x = \(\frac{3}{4}\)* 4
\(\frac{1}{4}\)+ x = \(\frac{12}{4}\)
\(\frac{1}{4}\)+ x = 3
x = 3 - \(\frac{1}{4}\)
x = \(\frac{11}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{3}{10}\div\frac{5}{9}+\frac{4}{15}\div\frac{1}{5}\)
\(=\frac{27}{50}+\frac{4}{3}\)
\(=\frac{281}{150}\)
5 phần 12
\(\frac{4}{24}+\frac{1}{4}\)
\(=\frac{4}{24}+\frac{6}{24}\)
\(=\frac{10}{24}\)
\(=\frac{5}{12}\)